DESIGN AND ANALYSIS OF A LOW COST SOLAR WATER PUMP FOR IRRIGATION IN BANGLADESH (Journal of Mechanical Engineering, 2014)
Bangladesh, a developing country of south-east Asia with large population has agricultural economy.About 59 percent cultivable land needs irrigation. During dry season and due to climate change, demand ofelectricity for electric power irrigation is increasing. Irrigation by electric power is cheaper than diesel pump.Due to severe shortage of electricity it is difficult to meet the demand. Harnessing solar power for irrigation is agood alternative to grid electricity. This paper deals with the design, technical and economic analysis of a lowcost 1 hp (746 W) small size dc photovoltaic water pumping system for irrigation. A buck converter is designedand constructed to improve the performance of the dc pump. All components of the system are procured locallyexcept the solar panels.DOI: http://dx.doi.org/10.3329/jme.v43i2.17833